A grand plan for earth love education in southern Africa: The dream becomes a nightmare. So, what went wrong? - Rob O'Donoghue (Environmental Association of Southern Africa, 1994)
The recent critique of the Council for the Environment (CFE) core syllabus for environmental education (Taylor et.al, 1993) worried many people active in environmental education. Few have disputed that the strategies and claims of the Council merited a critical response. What appears to have been most disturbing, however, is that the critique exposed possible error and myth within approaches to environmental education in southern Africa. This has shaken the spiritual solidarity of some environmental educators and features of environmental education programmes are being found conceptually wanting. In cases like this, where issues within a strongly held conventional wisdom are under review, critique can be extremely diftlcult. Fervent believers, spiritually committed to the cause, tend to reject criticism as academic or as simply a contesting opinion among many others of equal merit. Also, the adversity of the process may do little more than strengthen a resolve to resist outside criticism. Within this state of solidarity participants tend to be unable to separate error and untenable theoretical positions from the fundamental beliefs that they hold most dear. Any form of critique is consequently seen as a direct attack on the cause, in this case, an innate 'earth-love' purity of purpose intent on educating children in, about and for the environment.